TRANSFORMASI TEKS KABA KE NASKAH DRAMA CINDUA MATO KARYA WISRAN HADI: KAJIAN INTERTEKSTUAL - Alfalah, Adib; Elmustian, Elmustian; Syafrial, Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact: The background of this research based on a proverb saying that there is nothing new under the sun. Literary work will experience development and transforming. The problem is how the transformation of kaba text is into drama manuscript of Wisran Hadi’s Cindua Mato. The purpose of this researh is to reveal and explain the transformation of kaba Cindua Mato into drama manuscript of Wisran Hadi’s Cindua Mato. The benefits of this research are divided into theoretical, practical and educative. The used method of this research is the qualitative method which describe the descriptive data. The use d data collecting technique is library studies. The data resource of this research is kaba Cindua Mato written by Dt.Syamsuddin St. Radjo Endah and drama manuscript of Wisran Hadi’s Cindua Mato. The technique of data validity is using triangulation which is involving three validator. The whole data found by the writer from cindua mato drama manuscript are 76 data, and 48 data from Syamsuddin St. Radjo Endah’s kaba Cindua Mato as reference of transformation of a basic data(hipogram). Those data are clarified into three aspects of intrinsic element(character, background, theme) and event conflict which is presented in every plot of the story. Then again, each of data is clarified into three intertexttual categories(negation, affirmation, inovation). Those data are : in character aspect, there are negations with 4 data, affirmation with 0 data and inovations with 2 data. In background aspect, there are negation with 1 data , affirmation with 0 data and inovation with 5 data. In story conflict aspect, there are negations with 11 data, affirmations with 10 data, and inovations with 42 data.Key Words: Transformation, kaba, drama script.